In vitro cytotoxic potential of cow dung and expired tomato sauces-derived carbon nanodots against A-375 human melanoma cell line - Naik G.G.; Madavi R.; Minocha T.; Mohapatra D.; Pratap R.; Shreya S.; Patel P.K.; Yadav S.K.; Parmar A.; Patra A.; Jain N.S.; Satpathy S.; Kazi M.; Hussain M.D.; Sahu A.N. (My University, 2025)
Converting biowaste into a functional product is put to the test by the growing amount of biowaste in the world and the environmental problems it causes. In this research study, we synthesized, characterized, and evaluated bluish-green luminescent carbon nanodots (CNDs) from cow dung and expired tomato sauces via a hydrothermal synthesis method at 160 °C for 8 h. The carbon nanodots were fabricated without additional passivating agents and exhibited good physicochemical and optical properties. The intrinsic properties of carbon nanodots were characterized using various spectral techniques. First, we evaluated the cytotoxic potential of carbon nanodots against A-375 human melanoma cell lines. This study revealed that carbon nanodots exhibited potent cytotoxicity and significantly inhibited the proliferation of A-375 cells in a dose-dependent manner. Next, we demonstrated these carbon nanodot's free radical scavenging potential by employing 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The bluish-green fluorescent carbon nanodots fabricated using a green synthesis approach have broad potential for biological applications. © 2023 The Authors